Soil and water quality of an acid sulfate soil area and their effects on the growth of rice in the Kelantan Plains, Malaysia - Mohammed Ali, Payman Hassan (2016)
Agricultural practices that depend on identifying soil quality has an effective role in sustaining plant growth. Soil quality has direct and indirect effects on water quality, plant growth, and the environmental. Acid sulfate soils are widespread along the coastal plains of the Malay Peninsula. Planting rice in these types of soils has some challenges as it has low pH, contains toxic amounts of Al and Fe, and inadequate amounts of Ca, Mg and K. This study focused on studying the quality of acid sulfate soils and their effects on both field water quality and rice production. The field under study was at Kg. Golok, Kemasin-Semerak, Kelantan, Peninsular Malaysia. The study was conducted in three stages. The first stage was a preliminary investigation about the important properties of acid sulfate soils by taking soil samples randomly from surface (0-15cm) and sub-surface soil (15-30 cm) in twelve plots. Second stage was a detailed analysis of soil quality using some physical and chemical indicators. In addition, various physical and chemical indicators of the soil were selected to assess soil quality to ensure the functionality of acid sulfate soil. The physical indicators were texture, bulk density, and particle density. Thus, for chemical indicators, soil pH, EC, CEC, N, P, K, Ca, Mg, Al, and total N, C, and S were determined. Then, was followed by detailed water quality analysis to study the effect of acid sulfate soil on field water quality by taking ten surface water samples randomly from different places in the area under the study to see the impacts of acid sulfate materials on field water quality. Oxidation of acid sulfate soils form sulphuric acid, which will result in releasing metals, acidity, and nutrients into the soil, surface water, and ground water. These surface water sample were collected and analysed for pH, EC, cations (Ca, Mg, K, Al and Fe), anions (F, Cl, Br, NO2, NO3, PO4, and SO4), and heavy metals (As, Cd, Cr, Cu, Mn, Pb, and Zn). The final stage involved conducting a glasshouse experiment at Universiti Putra Malaysia, in five treatments with three replications. The treatments were ground magnesium limestone (GML) at rates 0, 2, and 4 t/ha. They were with and without organic fertilizer at rates 0 and 0.25 t/ha. Rice variety MR 219 was tested in this study. Glasshouse experiment was done by CRD, which was replicated three times. After one month of adding lime and organic fertilizer, the soil samples were analyzed to determine the effect of adding lime with organic fertilizer in changing the quality of acid sulfate soil, and to determine how it enhance the growth of rice. The results gained from this study showed that physical properties of acid sulfate soils were in appropriate conditions for planting rice. The texture of the soil was silty clay loam to clay loam. This type of texture has more capacity for water retention to fill the need of rice from water. Bulk density seems be at good levels. Thus, it is a very important property affecting the structural support, water and solute movement, and the soil aeration. Chemically, as these types of soils contain pyrite and due to its oxidation process, high acidity (pH 3-4) with toxic amounts of aluminum and iron will be released into the environment, making these soils infertile for plant growth if it is not ameliorated with an appropriate amendment. The infertility of these types of soils came as a result of high acidity (pH 3-4). Exchangeable Al was high in most plots, which reached 9.87 cmolc/kg. The concentration of Al was much higher than the critical level for rice production. Thus, they contained low amounts of essential nutrients for plant growth. Fe concentration ranged from 134 to 335 mg/kg. The initial top soil exchangeable Ca was less than 2 cmolc/kg soil, which is the required level for rice growth. Exchangeable Mg was almost less than 1 cmolc/kg, which is the required level. Field water quality was strongly affected by acid sulfate materials through decreasing pH, which in most samples was less than 4. Most cations were in water samples: Ca concentration ranged from 26.22-48.71 mg/L, Mg ranged from 13.75-17.82 mg/L, while Al ranged from 203.07-465.76 μM. Iron ranged from 77.46 to 163.90 μM. Furthermore, most anions were lower than the critical levels, except for chloride that had a high value ranging from 20.10 to 47.42 mg/L. Sulfate was very high in all water samples ranged from 283.80-629.80 mg/L, which is mainly due to the composition of acid sulfate soils of sulfate. Nitrate ranged from 1.09-3.90 mg/L. Generally, heavy metals were low in concentration, indicating that acid sulfate soil deposits did not release extra amounts of heavy metals into water bodies that have a problematic impact on soil, plant, and the environment. Manganese (Mn) ranged from 0.198-0.906 mg/L, zinc (Zn) ranged from 0.018-0.191 mg/L, aluminium (Al) ranged from 0012-0.077 mg/L, and copper (Cu) ranged from 0.020-0.087 mg/L. Glasshouse experiment results showed that rice yield was significantly increased by adding lime with organic fertilizer (P < 0.05). Liming had a clear role in increasing pH and essential nutrients, and in decreasing the toxic amounts of Al in the soil. Applying GML at the rate of 4 t/ha in combination with organic fertilizer, increased soil pH from 3.73 to 5.45 and Ca concentration from 0.37 to 1.53 cmolc/kg, and decreased Al concentration from 2.52 to 1.87 cmolc/kg. The findings of this project suggested the quality of acid sulfate soil has many problems that should be treated to be used for rice production, and the best management practice to help reducing problematic effects of these problems is adding ground magnesium limestone in combination with organic fertilizer. In addition, water quality of acid sulfate area has significantly affected by sulfuric materials in an acid sulfate soils. Adding lime, particularly GML in combination with organic fertilizer at the rate of 4 t/ha had positive effects in improving the quality of these soils.